Influência do grupo carboxílico na atividade citotóxica e na interação de novos complexos de rutênio com DNA e HSA - Araujo Neto, João Honorato de (2016)
The purpose of this work is evaluate how the position of a free carboxyl group can affect the interaction with DNA and HSA, and the cytotoxic profile against tumor and normal cells and Mycobacterium tuberculosis, for a set of complexes of ruthenium (II) derived for the 2,3; 2,4; 2,5, and 2,6-pyridinedicarboxylic acids. We show the synthesis, characterization and evaluation of biological properties of five new compounds with general formula [Ru(N-O)(dppb)(bipy)]PF6, where: N-O = 2,3-pyridinedicarboxylic acid (2,3); 2,4-pyridinedicarboxylic (2,4); 2,5-pyridinedicarboxylic acid (2,5); 2,6-pyridinedicarboxylic acid (2,6) and 2-carboxy-4-ethoxycarbonyl-pyridine acid (2,4e); dppb = 1,4-bis-diphenylphosphinobutane and bipy = 2,2'-bipyridine. The complex containing the ligand 2,4e was synthesized through esterification from the complex containing the ligand 2,4 and the complex [Ru(pic)(dppb)(bipy)]PF6 (pic = picolinic acid) was synthetized to compare the biological results. All compounds were characterized by nuclear magnetic resonance (1D - 31P(1H), 1H, 13C(1H) and 2D - DEPT-135, COSY and HSQC) cyclic voltammetry and differential pulse, elemental analysis, molar conductance, UV-vis and infrared spectroscopy and X-ray diffraction. DNA interaction studies carried by viscosity measurements, spectrophotometric titration and square-wave voltammetry do not evidence interactions between the compounds containing the ligands 2,3; 2,4; 2,5 and 2,6 and the DNA. We attribute this to the repulsion among the carboxyl free groups (as carboxylate groups at the working pH) and the DNA phosphate groups. In contrast, the compounds containing the ligands pic and 2,4e interacted with DNA showing interaction constants around 103 from the spectrophotometric titration; do not changing the DNA viscosity and decreasing the current and potential of the redox couple Ru(II)/Ru(III), characteristic responses of electrostatic interactions. In the interaction studies with HSA, through fluorometric titrations, the compounds containing the ligands 2,3; 2,4; 2,5 and 2,6 exhibit interaction constants (Kb) in the order of 104-106, while the compounds with pic and 2,4e ligands showed weaker interactions (aprox. 103). For all cases, the interaction mechanism is static and are involved hydrophobic forces. Cytotoxicity was availed in two tumor cell lines from breast cancer (MDA-MB-231 and MCF7), one tumor cell line from lung cancer (A549) and one healthy cell line from normal chinese hamster fibroblast (V79). The complex containing free carboxyl do not show cytotoxicity against any of the tested cells, since the complex containing the pic or 2,4e ligands were active, displaying IC50 values in the order of 5,1 µM and 3,4 of selectivity índex (MCF7), a significant lower value in contrast to cisplatin. In tests anti-Mycobacterium tuberculosis, only compounds containing ligands pic and 2,4 were active, showing MIC values lower than ethambutol, first-line drug used to treat tuberculosis. Partition coefficients denote a low lipophilicity for all the compounds containing the free carboxylic group, behavior that can explain the cytotoxic profiles obtained.